USA Basketball (2008)
Based in Colorado Springs, Colo., USA Basketball is a non-profit organization and the national governing body for men's and women's basketball in the United States. As the recognized governing body for basketball in the United States by the International Basketball Federation (FIBA) and the United States Olympic Committee (USOC), USA Basketball is responsible for the selection, training and fielding of USA teams that compete in FIBA sponsored international basketball competitions, as well as for some national competitions.